A PHARMACIST INTERVENTION ON KNOWLEDGE AND ADHERENCE IN PATIENTS WITH OPEN-ANGLE GLAUCOMA - KARN, DEEPA KUMARI; GURUNG, SHILA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the study is to assess the pharmacist’s intervention on knowledge and adherence in patients with open-angle glaucoma therapy. Methods: The study was conducted at the glaucoma outpatient department of Shree Rana Ambika Shah Eye Hospital, Rupandehi, Nepal. Census sampling was performed among the glaucoma patients meeting the inclusion criteria from August 2018 to November 2018. Data were collected using a structured questionnaire that included questions about demography, knowledge of glaucoma, medication adherence, and factors associated with medication non-adherence to glaucoma therapy. Each patient was counseled by a pharmacist, and the relevant information was provided in the form of an information leaflet. Knowledge level and adherence level were re-assessed during the follow-up visit after 1 month. The Morisky–Green–Levine medication adherence scale was used to assess adherence. Results: A total of 103 patients were enrolled in the study, and the majority of the patients were of age ≥59 years. After intervention by the pharmacist, the knowledge level on glaucoma improved from poor to good. Before intervention, about 31% of patients were adherent to the medication therapy, but after intervention, about 73% of patients were adherence to the medication therapy. There was a significant difference in the mean of the knowledge level score and the mean of the medication adherence score before and after intervention. The common causes of non-adherence were reported to be forgetfulness, a stressful life, and difficulties with medication time. Conclusion: The study demonstrates that pharmacist intervention is effective in improving both knowledge and medication adherence to open-angle glaucoma therapy.